Clinical and Molecular Phenotypes of Low‐Penetrance Variants of NLRP3: Diagnostic and Therapeutic Challenges. Issue 11 (17th October 2017) - Kuemmerle‐Deschner, J. B.; Verma, D.; Endres, T.; Broderick, L.; de Jesus, A. A.; Hofer, F.; Blank, N.; Krause, K.; Rietschel, C.; Horneff, G.; Aksentijevich, I.; Lohse, P.; et al.
Abstract : Objective: Cryopyrin‐associated periodic syndromes (CAPS) result from gain‐of‐function mutations in the NLRP3 gene, which causes excessive release of interleukin‐1β (IL‐1β) and systemic inflammation. While pathogenetic NLRP3 variant phenotypes are well‐characterized, low‐penetrance NLRP3 variants represent a significant clinical challenge. The aims of this study were to determine the clinical phenotype, the in vitro biologic phenotype, and the effect of anti–IL‐1 treatment in patients with low‐penetrance NLRP3 variants. Methods: A multicenter study of consecutive symptomatic patients with low‐penetrance NLRP3 variants recruited from 7 centers between May 2012 and May 2013 was performed. The observed findings were transferred into a study database, from which they were extracted for analysis. Controls were patients with a known pathogenetic NLRP3 variant. Clinical presentation and CAPS markers of inflammation were captured. Functional assays of inflammasome activation, including caspase 1 activity, NF‐κB release, cell death, and IL‐1β release, were performed. Treatment effects of IL‐1 were determined. Comparisons between low‐penetrance and pathogenetic NLRP3 variants were performed. Results: The study included 45 patients, 21 of which were female (47%); 26 of the patients (58%) were children. NLRP3 low‐penetrance variants identified in the patients were Q703K (n = 19), R488K (n = 6), and V198M (n = 20). In the controls, 28 had pathogenetic NLRP3 variants. Patients with low‐penetrance NLRP3 variants had significantly more fever (76%) and gastrointestinal symptoms (73%); eye disease, hearing loss, and renal involvement were less common. Functional inflammasome testing identified an intermediate phenotype in low‐penetrance NLRP3 variants as compared to wild‐type and pathogenetic NLRP3 variants. All treated patients responded to IL‐1 inhibition, with complete response documented in 50% of patients. Conclusion: Patients with low‐penetrance NLRP3 variants display a distinct clinical phenotype and an intermediate biologic phenotype, including IL‐1β and non–IL‐1β–mediated inflammatory pathway activation.